Recent Understanding and Future Directions of Recurrent Corticotroph Tumors - Hinojosa Amaya, José Miguel; Lam Chung, César Ernesto; Cuevas Ramos, Daniel (Frontiers Research Foundation, 2021)
Corticotroph tumors (CTs) are pituitary neoplasms arising from the Tpit lineage, which may or not express adrenocorticotrophic hormone (ACTH). Functioning CTs cause Cushing’s disease (CD), which has high morbidity and mortality due to hypercortisolemia. “Non-functioning” or silent CTs (SCT) and the Crooke’s cell subtypes do not cause CD and may be asymptomatic until manifested by compressive symptoms and are more frequently found as macroadenoma. Both tend toward more aggressive behavior, recurrence, and a higher rate of malignant transformation to pituitary carcinoma. Tumorigenesis involves genetic, epigenetic, and post-transcriptional disruption of cell-cycle regulators, which increase cell proliferation, POMC overexpression, ACTH transcription, and/or hypersecretion. Furthermore, functioning CTs develop resistance to glucocorticoid-mediated negative feedback on ACTH secretion, through increased expression of testicular orphan nuclear receptor 4 (TR4), heat-shock protein 90 (HSP90), and loss-of-function mutation of CDK5 and ABL enzyme substrate 1 (CABLES1) gene. Overt autonomous hypercortisolemia is difficult to control, and multiple diagnostic studies and therapeutic modalities are commonly required. Cell-cycle regulation depends mainly on p27, cyclin E, cyclin-dependent kinases (CDKs), and the retinoblastoma protein (Rb)/E2F1 transcription factor complex. Gain-of-function mutations of ubiquitin-specific protease (USP) 8, USP48, and BRAF genes may subsequently cause overexpression of epithelial growth factor receptor (EGFR), and enhance POMC transcription, cell proliferation, and tumor growth. Epigenetic changes through micro RNAs and decreased DNA deacetylation by histone deacetylase type 2 (HDAC2), may also affect tumor growth. All the former mechanisms may become interesting therapeutic targets for CTs, aside from temozolomide, currently used for aggressive tumors. Potential therapeutic agents are EGFR inhibitors such as gefitinib and lapatinib, the purine analog R-roscovitine by dissociation of CDK2/Cyclin E complex, the HSP90 inhibitor silibinin (novobiocin), to reduce resistance to glucocorticoid-mediated negative feedback, and BRAF inhibitors vemurafenib and dabrafenib in BRAF V600E positive tumors. This review summarizes the molecular mechanisms related to CTs tumorigenesis, their diagnostic approach, and provides an update of the potential novel therapies, from the lab bench to the clinical translation.